Assessment of the Banff Working Group classification of definitive BK polyomavirus nephropathy. (2nd September 2021) - Kowalewska, Jolanta; El Moudden, Ismail; Perkowska‐Ptasinska, Agnieszka; Kapp, Meghan E.; Fogo, Agnes B.; Lin, Mercury Y.; Mirza, Alamgir; Troyer, Dean A.; Durlik, Magdalena; Sandhu, Rana; Ciszek, Michal; Deborska‐Materkowska, Dominika; et al.
Summary: Polyomavirus associated nephropathy (PyVAN) continues to be a burden in renal transplantation leading to allograft insufficiency or graft failure. A presumptive diagnosis of PyVAN is made based on the presence of BK polyomavirus in patients' plasma; however, kidney biopsy remains the gold standard to establish a definitive diagnosis. The Banff Working Group on PyVAN proposed a novel classification of definitive PyVAN based on polyomavirus replication/load level and the extent of interstitial fibrosis. The aim of our study was to test the newly defined classes of PyVAN using independent cohorts of 124 kidney transplant patients with PyVAN with respect to the initial presentation and outcome, and to compare our analysis to that previously reported. Detailed analysis of our cohort revealed that the proposed classification of PyVAN did not stratify or identify patients at increased risk of allograft failure. Specifically, while class 3 was associated with the worst prognosis, there was no significant difference between the outcomes in classes 1 and 2. We also found that the timing post‐transplantation and inflammation in areas of interstitial fibrosis and tubular atrophy might be additional factors contributing to an unfavorable allograft outcome in patients with PyVAN. Abstract : Our validation study of Banff classification of definitive polyomavirus‐associated nephropathy (PyVAN) failed to confirm its predictive value. The timing post‐transplantation and inflammation in areas of interstitial fibrosis and tubular atrophy might be additional factors contributing to an unfavorable allograft outcome in patients with PyVAN.